10 years of international albinism awareness: United Nations celebrate an anniversary and a decade of collective progress, but challenges remain - Rappold, Gudrun (Medizinische Genetik, 2024)
Der Artikel 10 Years of International Albinism Awareness wurde am 30. September 2024 in der Zeitschrift Medizinische Genetik (Band 36, Heft 3) veröffentlicht.
Gesehen am 07.02.2025